Sibling Rivalry: A Six Country Comparison - Stefan C. Wolter (Institute for the Study of Labor (IZA), 2003)
In this paper we analyse with the PISA data on literacy achievement of fifteen-year-old pupils in six member countries of the OECD, whether the fact of having many siblings affects the individual educational outcome. The hypothesis that we test is whether parents? resources matter for educational outcome. If they do and parents are constraint in their budgets, siblings will rival for the limited parental resources and thereby negatively affect educational outcome. The hypothesis is tested by regressing the literacy achievement on the number of siblings within a family and also by regressing directly forms of parental resources on the family size. We find significant family size effects in all six countries analysed but we also find significant differences in the effects between countries. Although sibling rivalry is relevant in all countries, it seems that some countries can compensate better than others and thereby achieve higher equity in the educational system.
Keywords: I2; J2; D1; 330; education; equity; parental background; family-size; PISA; Bildungsniveau; Familiensoziologie; Schätzung; Vergleich; Belgien; Kanada; Finnland; Frankreich; Deutschland; Schweiz